CSI511 - Management Information Systems Februari 1999 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1999)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 1998/99 February 1999 CSI511 - Management Information Systems Duration : [3 hours] INSTRUCTION TO CANDIDATE: • Please ensure that this examination paper contains SIX questions in THREE printed pages before you start the examination. • Answer FOUR questions only. • You can choose to answer either in Bahasa Malaysia or English.